THE LEGAL STATUS OF A CHILD BORN OUT OF WEDLOCK IN THE PERSPECTIVE OF SYAFI’I AND HANAFI SCHOOLS - Rizka A. R, Nyrza; B, M. Taufan; Amelia, Yuni (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2023)
Promiscuity among young people, as happened today, often leads to unexpected things, namely the occurrence of pregnancy before marriage. If a child was born illegitimately, he was usually called a child born out of wedlock (natural child). As a result, he cannot be connected to his father but only to his mother. According to Syafi'i School, a child born out of wedlock is born less than six months after intercourse with a legal husband. The child's legal status does not have a lineage relationship with his biological father because he was born outside of a legal marriage. Meanwhile, according to the Hanafi School, a child born out of wedlock is born less than six months after the marriage contract. The legal status of children born out of wedlock is the same as children born in a legal marriage because the Hanafi School considers the existence of lineage in essence. The main difference between the two is in their understanding and interpretation of the sources of Islamic law related to the status of a child born out of wedlock. There is a difference because in term of history, in term of sociology, and in term of culture.